2017
DOI: 10.1039/c6nj03052a
|View full text |Cite
|
Sign up to set email alerts
|

A permittivity regulating strategy to achieve high-performance electromagnetic wave absorbers with compatibility of impedance matching and energy conservation

Abstract: With the variation of permittivity, MoS2/rGO composites with a broad frequency bandwidth and strong absorbing performance can be obtained due to their optimal compatibility of impedance matching and attenuation loss ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(70 citation statements)
references
References 47 publications
1
69
0
Order By: Relevance
“…The minimum RL value of −67.1 dB could be obtained at 14.8 GHz, and the effective EA bandwidth could cover 5.92 GHz (12.08-18.00 GHz). The results fully demonstrated that Quan's [23] work acquired absorber with strong attenuation ability and suitable impedance matching simultaneously. Feng et al [37] constructed an rGO/ZnO composite through an in situ crystallization approach.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…The minimum RL value of −67.1 dB could be obtained at 14.8 GHz, and the effective EA bandwidth could cover 5.92 GHz (12.08-18.00 GHz). The results fully demonstrated that Quan's [23] work acquired absorber with strong attenuation ability and suitable impedance matching simultaneously. Feng et al [37] constructed an rGO/ZnO composite through an in situ crystallization approach.…”
Section: Introductionmentioning
confidence: 66%
“…Carbon materials are representative absorbers, beneficial for their dielectric loss, but the high value of their conductivity from this kind material always makes their impedance mismatch [20][21][22]. According to a previous report [23], the calculated minimum reflection loss (RL) of graphene can hardly reach up to −10 dB. As a traditional absorber, ferromagnetic materials have been used since the First World War.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that the ε′ of the ICF rises slowly and then remains basically stable, while the ε′ of both 3D-ISF-I and 3D-ISF-II show downtrend. It is reported that the decrease of ε′ and the frequency dispersion effect are favorable for the microwave absorption [32]. With increment of the SiC layer thickness, the variation trend of ε′ of 3D-ISF-II is almost the same as that of 3D-ISF-I except a slight decrease.…”
Section: Electromagnetic Propertymentioning
confidence: 87%
“…They are the impedance matching, which requires permittivity and permeability of the material to be nearly equal and the other is energy conservation which requires the microwave absorbers to undergo strong propagation losses. The attenuation constant (α) gives the extent of propagation losses in the shield . According to transmission line theory, the integral attenuation loss ability of microwave absorbers can be given by, trueα=2πfc×(μ"ϵ"-μ'ϵ')+(μ"ϵ"-μ'ϵ')2+(μ'ϵ"-μ"ϵ')2 …”
Section: Effect Of Alloy/ Mwnt Heterostructure Particles On Electromamentioning
confidence: 99%